2007
DOI: 10.1021/ja069295s
|View full text |Cite
|
Sign up to set email alerts
|

The Solvent Cage Effect:  Is There a Spin Barrier to Recombination of Transition Metal Radicals?

Abstract: This investigation explored whether there is a spin barrier to recombination of first- and second-row transition metal-centered radicals in a radical cage pair. To answer this question, the recombination efficiencies of photochemically generated radical cage pairs (denoted as FcP) were measured in the presence and absence of an external heavy atom probe. Two methods were employed for measuring the cage effect. The first method was femtosecond pump-probe transient absorption spectroscopy, which directly measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 90 publications
2
31
0
Order By: Relevance
“…The intercalation of solvent molecules between organometallic radical pairs has been directly observed to occur in the picosecond time regime. [19,20] Rapid reorganization of active-site water is also thought to be involved in the complicated diffusional kinetics that occur after photodissociation of heme protein axial ligands. [21,22] For photodissociated [heme-Fe II NO] and [heme-Fe II O 2 ] in myoglobin, ligand recombination and cage escape are competitive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercalation of solvent molecules between organometallic radical pairs has been directly observed to occur in the picosecond time regime. [19,20] Rapid reorganization of active-site water is also thought to be involved in the complicated diffusional kinetics that occur after photodissociation of heme protein axial ligands. [21,22] For photodissociated [heme-Fe II NO] and [heme-Fe II O 2 ] in myoglobin, ligand recombination and cage escape are competitive.…”
Section: Methodsmentioning
confidence: 99%
“…The intercalation of solvent molecules between organometallic radical pairs has been directly observed to occur in the ps time regime. [19,20] Rapid reorganization of active site water is also thought to be involved in the complicated diffusional kinetics that occur after photodissociation of heme protein axial ligands. [21,22] [23] Thus, even though there is almost no enthalpic barrier to ligand recombination, there is an entropic driving force that favors ligand diffusion into adjacent protein cavities where NO, for example, is observed to persist for up to a nanosecond.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two sequential radical reactions similar to those proposed here could be helpful for rationalizing the results obtained by Harris et al for the recombination efficiencies of photochemically generated radical cage pairs containing Mo, Fe, and Ti in viscous solvents. These authors have suggested that no spin barrier exists to radical–radical recombination . Although not conclusive because the matrix has not been modeled explicitly, this scheme could represent an alternative to the two‐state and multistate reactivity models for the theoretical description of reaction systems involving transition‐metal species in confined media.…”
Section: Resultsmentioning
confidence: 99%
“…These authors have suggested that no spin barrier exists to radical-radical recombination. [40] Although not conclusive because the matrix has not been modeled explicitly, this scheme could represent an alternative to the two-state and multistate reactivity models for the theoretical description of reaction systems involving transition-metal species in confined media. [41,42] Conclusions A theoretical study using a gas-type model for the reactions Zr 1 CH 3 F and Zr 1 CH 3 CN was performed to rationalize the product distributions revealed from IR matrix-isolation determinations.…”
Section: Full Papermentioning
confidence: 99%
“…Tyler and coworkers investigated the presence of a spin barrier to the geminate recombination 17-electron radicals in complexes of Fe, Mo, and Ti. 29 Recombination efficiencies were found to be similar in the presence or absence of an external heavy atom perturber, from which it was concluded that no spin barrier was present; another possible interpretation exists, which is that an external heavy atom effect may not have been significantly observed. A combined experimental/computational study by our group also investigated the activation of stannanes (Sn-H bonds) by a series triplet, first-row transition metal reaction intermediates.…”
Section: Introductionmentioning
confidence: 97%